Orthodontic movement of endodontically treated teeth - Alberto Consolaro; Renata Bianco Consolaro (Dental Press Editora, 2013)
Often there is the need of moving teeth endodontically treated or teeth still in endodontic treatment. In order to collaborate with the comprehension and substantiation of the following subjects will be discussed: 1) Orthodontic movement in endodontically treated teeth without periapical lesion, 2) Orthodontic movement in endodontically treated teeth with inflammatory periapical lesion, and 3) Orthodontic movement in teeth endodontically treated due to aseptic pulp necrosis by dental trauma. In practically all situations, endodontically treated teeth to be orthodontically moved must be subjected to a careful evaluation by the endodontist about the conditions, adequate or not, of the endodontic treatment. Then, in this paper it was sought to induce an insight for new clinical researches about the theme that may definitely prove the information obtained by interrelations of information in parallel to clinical practice.